Human Wharton’s Jelly Stem Cell Secretions Inhibit Human Leukemic Cell Line K562 in vitro by Inducing Cell Cycle Arrest and Apoptosis - Huwaikem, Muneerah A. H.; Kalamegam, Gauthaman; Alrefaei, Ghadeer; Ahmed, Farid; Kadam, Roaa; Qadah, Talal; Sait, Khalid H. W.; Pushparaj, Peter N. (Frontiers in Cell and Developmental Biology, 2021)
Emerging resistance to the tyrosine kinase inhibitors that target the BCR-ABL1 oncoprotein, has prompted research for novel therapeutics against chronic myeloid leukaemia (CML). Herein we evaluated the tumour inhibitory properties of human Wharton’s jelly stem cells (hWJSCs) co-culture (hWJSC-CC) and its extracts namely, the hWJSC-conditioned medium (hWJSC-CM, 100%) and hWJSC-lysate (hWJSC-L; 15 µg/ml) on a CML cell line K562 in vitro. The derived hWJSCs expressed MSCs related CD markers and demonstrated mesodermal tissue differentiation potential. The cell metabolic activity showed a mean maximal decrease in K562 cells by 49.12%, 41.98% and 68.80% following treatment with hWJSC-CC, hWJSC-CM, and hWJSC-L at 72 h. The sub-G1 population in cell cycle was decreased by 3.2%, 4.5% and 3.8% following treatment with hWJSC-CC, hWJSC-CM and hWJSC-L; while the G2/M cell population was increased by 13.7% and 12.5% with hWJSC-CM and hWJSC-L respectively at 48 h. AnnexinV-APC assay showed an increase in the apoptotic cells by 4.0%, 3.9% and 4.5% at 48 h. The expression of pro-apoptotic BAX and CASP3 genes were increased, while BIRC5 (Survivin) was decreased compared to the control. The pro-inflammation related genes namely IFN-γ, TNF-α, IL-1β, IL-6, IL-8 and IL-12A were decreased while the anti-inflammatory genes namely IL-4 and IL-10 were increased following treatment with hWJSC-CC, hWJSC-CM and hWJSC-L at 48 h. Multiplex bead-based cytokine assay also demonstrated decreases in the pro-inflammatory cytokines (IFN-γ, TNF-α, IL-1β, IL-6, and IL-12) and an increase in the anti-inflammatory cytokine IL-10 compared to the control. The pro-inflammatory cytokine IL-8 showed an increase with hWJSC-CC and decreases with both hWJSC-CM and hWJSC-L. The hWJSCs and its extracts inhibited the K562 cells by causing cell cycle arrest and inducing apoptosis via the soluble cellular factors. However, an in vivo evaluation is necessary to unravel the true potential of hWJSCs and its extracts before its use in CML inhibition.